Engineering and Optimization of Silicon–Iron–Manganese Nanoalloy Electrode for Enhanced Lithium-Ion Battery - Alaboina, Pankaj K.; Cho, Jong-Soo; Cho, Sung-Jin (Nano-Micro Letters, 2017)
The electrochemical performance of a battery is considered to be primarily dependent on the electrode material. However, engineering and optimization of electrodes also play a crucial role, and the same electrode material can be designed to offer significantly improved batteries. In this work, Si–Fe–Mn nanomaterial alloy (Si/alloy) and graphite composite electrodes were densified at different calendering conditions of 3, 5, and 8 tons, and its influence on electrode porosity, electrolyte wettability, and long-term cycling was investigated. The active material loading was maintained very high ( 2 mg cm−2) to implement electrode engineering close to commercial loading scales. The densification was optimized to balance between the electrode thickness and wettability to enable the best electrochemical properties of the Si/alloy anodes. In this case, engineering and optimizing the Si/alloy composite electrodes to 3 ton calendering (electrode densification from 0.39 to 0.48 g cm−3) showed enhanced cycling stability with a high capacity retention of 100% over 100 cycles. Highlights: 1 Si–Fe–Mn alloy (Si/alloy) electrodes with high loading of 2 mg cm−2 were calendered at 3, 5, and 8 tons pressure and investigated on porosity, wettability, and electrochemical properties. 2 Electrode engineering and wettability optimization balance are necessary to realize the true electrochemical potentials of the battery materials.